2007
DOI: 10.1111/j.1835-2561.2007.tb00443.x
|View full text |Cite
|
Sign up to set email alerts
|

Financial Statement Fraud: Some Lessons from US and European Case Studies

Abstract: This paper studies 14 companies which were subject to an official investigation arising from the publication of fraudulent financial statements. The research found senior management to be responsible for most fraud. Recording false sales was the most common method of financial statement fraud. Meeting external forecasts emerged as the primary motivation. Management discovered most fraud, although the discovery was split between incumbent and new management.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
50
0
7

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(65 citation statements)
references
References 17 publications
0
50
0
7
Order By: Relevance
“…4 For instance, Brennan and McGrath (2007) on the basis of 14 fraud cases, focus on incentives and opportunities. 5 Uzun et al (2004) also used cases as identified in the financial press, but with a focus on governance mechanisms.…”
Section: Future Researchmentioning
confidence: 99%
“…4 For instance, Brennan and McGrath (2007) on the basis of 14 fraud cases, focus on incentives and opportunities. 5 Uzun et al (2004) also used cases as identified in the financial press, but with a focus on governance mechanisms.…”
Section: Future Researchmentioning
confidence: 99%
“…National research studies around the world (Amat, Blake, 2006;Brennan, McGrath, 2007;Murphy 2011;or Henselmann, Hofmann, 2010;and Jones, 2010) show that there is a growing pressure in enforcing transparency and business ethics, which is true not only for publicly traded companies, but also for example the misuse of subsidies by prominent entities, substantiation in accounting. Demands are namely imposed on administrative bodies whose responsibility is to guarantee the development of corporate culture and to promote shared values inside the company.…”
Section: Methodsmentioning
confidence: 99%
“…The definition of financial reporting fraud according to the American Institute Certified Public Accountant 1998 is a deliberate act or omission which results in material misstatement that misleads the financial statements. In addition, according to the Australian Auditing Standards (AAS), financial reporting fraud is a negligence or intentional misinterpretation of a certain amount or disclosure in financial reporting to deceive users of financial statements [14,1].…”
Section: Fraud In Financial Reportingmentioning
confidence: 99%